Persentase Pemberian Pakan Ikan Rucah Yang Berbeda Terhadap Pertumbuhan Kepiting Bakau (Scylla spp) - Ahmad Hanif; Sri Herlina (Fakultas Peternakan Universitas Kristen Palangka Raya, 2021)
Mangrove crab (Scylla spp) is a fishery commodity that has important economic value. This study aims to determine the effectiveness of trash fish on the growth of mangrove crab with different percentages. The study used a completely randomized design (CRD) with 4 (four) treatments, namely treatment A feeding trash fish with 5%, treatment B feeding trash fish 10%, treatment C feeding trash fish 15% and treatment D feeding trash fish 20 %. The results showed that feeding trash fish with different percentages had a significant effect (P